2010
DOI: 10.1111/j.1551-2916.2010.03780.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical Behavior of Ceramic Green Bodies During Presintering

Abstract: A testing methodology, which includes the evaluation of free sintering strain, stress‐induced dimensional changes, and weight changes, was developed to determine the critical dimensional changes and thermomechanical response during presintering (i.e., before densification). The effects of organic binder burnout, decomposition of phases, and phase changes on the thermomechanical behavior of a ceramic green body, consisting of methylcellulose as a binder, gibbsite, silica, and alumina, were studied. The compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The thermomechanical behavior of ceramic bodies during debindering has been studied. It was found that removal of the organic binder phase leads to a fragile intermediate which is only held together by mechanical interlocking of particles (Gupta, 2010). Final debindering temperature is therefore often set above the level necessary to remove the binder in order to be able to safely handle the debindered bodies.…”
Section: Thermal Treatmentmentioning
confidence: 99%
“…The thermomechanical behavior of ceramic bodies during debindering has been studied. It was found that removal of the organic binder phase leads to a fragile intermediate which is only held together by mechanical interlocking of particles (Gupta, 2010). Final debindering temperature is therefore often set above the level necessary to remove the binder in order to be able to safely handle the debindered bodies.…”
Section: Thermal Treatmentmentioning
confidence: 99%